Concept paradoxal de « collective creation » dans l’avant-garde française: le rôle du groupe dans la création artistique - BALAKIREVA, Margarita (Studia Universitatis Babeș-Bolyai Dramatica, 2016)
Paradoxical Concept of Collective Creation in French Avant-Garde: the Role of the Group in Artistic Creation. This paper analyzes the importance of the group and of collective creation in the case of historical avant-garde not only from a social or a political point of view, but from an aesthetical one. The starting point is Tristan Tzara’s formula: “I write in order to search for people.” We will focus on many examples: Dada, surrealism, situationism, trying to underline the fact that for the members of these groups, the dialogue and the exchanges were as important as individual experiences in the artistic process.